Transit of Clowning Becomings in their Interrelations Between Circus and Theater - Mariana Augusta Azevedo Silva (Revista Brasileira de Estudos da Presença)
This article is based on the philosophical aspects imbricated in the interrelationships between circus, theater and clowning. A theoretical framework is approached in order to elucidate inter-agencies and zones of proximity established between the areas elaborated here. The work of the artist Gardi Hutter stands out as a place to apprehend the fluxes that run through the conjunction between these arts, using acrobatic techniques, object manipulation and illusionism, together with techniques inherent to clowning itself, and appropriating scenic lighting, scenery, costume and sound resources capable of constituting a transit of becoming that is established in the circus-theater-clowning context.